2003
DOI: 10.1038/oby.2003.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Sources on Satiety

Abstract: ALFENAS, RITA C.G. AND RICHARD D. MATTES. Effect of fat sources on satiety. Obes Res. 2003;11:183-187. Objective: There are inconsistent reports on the satiety value of different fatty acids. This study compared the appetitive effects of two fat sources rich in monounsaturated fatty acids (peanut oil and canola oil) with a source rich in saturated fatty acids (butter). Research Methods and Procedures:After an overnight fast, lean participants completed a questionnaire eliciting information about hunger, fullne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 37 publications
7
21
0
2
Order By: Relevance
“…Another study further revealed that PUFA, consumed as part of a meal, suppressed appetite more than MUFA or SFA, and resulted in lower consumption of a subsequent meal in 40 healthy adults. However, many other human studies have failed to document the differential effects of fat subtypes on human appetite reported by these two studies [49][50][51][52][53][54]. The lack of effects of PUFA on food intake was also supported by observations from animal studies [55,56].…”
Section: Appetite and Dietary Intakementioning
confidence: 71%
“…Another study further revealed that PUFA, consumed as part of a meal, suppressed appetite more than MUFA or SFA, and resulted in lower consumption of a subsequent meal in 40 healthy adults. However, many other human studies have failed to document the differential effects of fat subtypes on human appetite reported by these two studies [49][50][51][52][53][54]. The lack of effects of PUFA on food intake was also supported by observations from animal studies [55,56].…”
Section: Appetite and Dietary Intakementioning
confidence: 71%
“…21 Participants consumed significantly more energy in the first trial when provided the oleic acid, but no differences of intake were noted in the replication trial. A third trial 22 compared the effects of muffin preloads rich in peanut oil or canola oil (both high in MUFA) with muffins rich in butter (rich in SFA). No differential satiety effects of the fat sources were observed.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a physiological sensitivity to the fat ingestion, but not to fatty acid source or saturation. [20][21][22][23] A greater reduction of self-selected fat intake was noted with the safflower oil treatment. We can only speculate on an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that dietary fat is more satietogenic than other nutrients, few data concerning differences in the perception according to its saturation grade of fatty acids are available (18). It is known that MUFA are more promptly oxidized than SFA, which could result in higher satietogenic power; however, in humans, studies are inconclusive (19).…”
Section: Introductionmentioning
confidence: 99%